Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean - Lee, Jimin; Kim, Dongsung; Kim, Il-Hoi (Zootaxa, 2020)
Eight species of copepods belonging to the family Dirivultidae (Siphonostomatoida) are described from deep-water hydrothermal vent fields on the Central Indian Ridge in the Indian Ocean. Aphotopontius limatulus Humes, 1987, previously known only from the East Pacific, is included. The other seven species are new, as follows: Aphotopontius kiost n. sp., A. muricatus n. sp., Benthoxynus constrictus n. sp., Stygiopontius spinifer n. sp., S. horridus n. sp., S. geminus n. sp., and S. quadripaxillifer n. sp. The copepodid I stage of S. horridus n. sp. is also described. This is the first record on copepods living on hydrothermal vent fields in the Indian Ocean.